Recent Molecular Insights into Agonist-specific Binding to the Mu-Opioid Receptor - Zádor, Ferenc; Király, Kornél; Essmat, Nariman; Al-Khrasani, Mahmoud (Frontiers in Molecular Biosciences, 2022)
Opioid agonists produce their analgesic effects primarily by acting at the µ-opioid receptor (µOR). µOR agonists with different efficacy exert diverse molecular changes in the µOR which dictates the faith of the receptor’s signaling pathway and possibly it’s degree of desensitization. Since the development of the active conformations of the µOR, growing data has been published in relation to ligand specific changes in µOR activation. In this regards, this review, summarizing recent data regarding the most studied opioid agonists in in silico µOR activation, including how these ligands are recognized by the µOR, how their binding signal is transmitted towards the intracellular parts of the µOR and finally what type of large scale movements do these changes trigger in the µOR’s domains.